2011
DOI: 10.1136/gutjnl-2011-300798
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, but not oesophageal pH-impedance, profiles predict response to proton pump inhibitors in gastro-oesophageal reflux disease

Abstract: No reflux pattern demonstrated by 24 h pH-impedance monitoring is associated with response to PPIs in patients with GORD symptoms. In contrast, absence of oesophagitis, presence of functional digestive disorders and BMI ≤25 kg/m(2) are strongly associated with PPI failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
97
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(108 citation statements)
references
References 36 publications
8
97
0
3
Order By: Relevance
“…It has been revealed that 37%-60% of NERD patients have normal acid reflux, and the proportion of FH and RH can vary from less than 10% to 75% and to 36%, respectively. [14][15][16][17][18][19][20][21][22][23][24][25] One factor that has contributed to the variation is the changing definitions of heartburn phenotypes. For example, the Rome III committee used to define those with normal reflux but positive symptom-reflux association as NERD, but these patients were then isolated as a single group named RH in the updated criteria.…”
Section: Discussionmentioning
confidence: 99%
“…It has been revealed that 37%-60% of NERD patients have normal acid reflux, and the proportion of FH and RH can vary from less than 10% to 75% and to 36%, respectively. [14][15][16][17][18][19][20][21][22][23][24][25] One factor that has contributed to the variation is the changing definitions of heartburn phenotypes. For example, the Rome III committee used to define those with normal reflux but positive symptom-reflux association as NERD, but these patients were then isolated as a single group named RH in the updated criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported co-existing FD as a factor predicting PPI failure in GERD patients. Recently, Zerbib et al [20] reported that FD and irritable bowel syndrome are strongly associated with PPI failure in patients with documented reflux. However, there are no studies reporting factors that predict P-CAB failure.…”
Section: Discussionmentioning
confidence: 99%
“…Our results concur with those in the literature in that impedance monitoring detects more reflux events than pH monitoring. Although previous assessments suggest that the clinical value and optimal use of symptom-reflux correlation remain unclear (33,34), we demonstrate that SAP from impedance testing is an independent predictor of symptomatic outcome after medical therapy of GERD. Despite this finding, only limited outcome data exist to suggest a relationship between non-acidic reflux detected by impedance testing and symptoms in suspected GERD (35).…”
Section: Discussionmentioning
confidence: 53%